2019
DOI: 10.3390/ijms20030458
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Tissue-Specific Origins Affects Their Responsiveness to TGF-β2 during Endothelial-to-Mesenchymal Transition

Abstract: The endothelial-to-mesenchymal transition (EndMT) is a biological process where endothelial cells (ECs) acquire a fibroblastic phenotype after concomitant loss of the apical-basal polarity and intercellular junction proteins. This process is critical to embryonic development and is involved in diseases such as fibrosis and tumor progression. The signaling pathway of the transforming growth factor β (TGF-β) is an important molecular route responsible for EndMT activation. However, it is unclear whether the anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…IPF is a progressive, chronic, and ultimately fatal interstitial lung disease characterized by enhanced extracellular matrix deposition. Although the exact etiology in IPF is unclear, complex, and probably diverse, previous studies have identified EndoMT as one of the important processes for the establishment and progression of the fibrotic changes . In our study, we also found that all control groups showed no abnormalities, while WT‐BLM mice showed significant fibrotic responses in the lung; these were accompanied by decreased endothelial markers VE‐cadherin and CD31 but increased mesenchymal cell marker α‐smooth muscle actin (α‐SMA), indicating EndoMT.…”
Section: Discussionsupporting
confidence: 70%
“…IPF is a progressive, chronic, and ultimately fatal interstitial lung disease characterized by enhanced extracellular matrix deposition. Although the exact etiology in IPF is unclear, complex, and probably diverse, previous studies have identified EndoMT as one of the important processes for the establishment and progression of the fibrotic changes . In our study, we also found that all control groups showed no abnormalities, while WT‐BLM mice showed significant fibrotic responses in the lung; these were accompanied by decreased endothelial markers VE‐cadherin and CD31 but increased mesenchymal cell marker α‐smooth muscle actin (α‐SMA), indicating EndoMT.…”
Section: Discussionsupporting
confidence: 70%
“…Unlike HUVEC, HMEC-1 do not respond mechanically to addition of TGF-β2, a discrepancy which is consistent with TGF-β2 not being a stiffness-sensitive DEG for HMEC-1. Different EC types are well known to exhibit local morphological and functional specializations and distinct gene expression profiles depending on the tissue they originate from 75 and can therefore respond differently to cytokines including TGF-β2 76 . Which EC types are sensitive to TGF-β2 and how much that depends on the anatomical location they come from or their local microenvironment, including its mechanics, could be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ treatment of PAECs induces the expression of the EndoMT transcription factors TWIST1 and SNAIL1 [ 103 , 108 ] and the mesenchymal markers α-SMA and phospho-vimentin [ 109 ] ( Figure 4 ). TWIST1 increases the expression of TGFβ, leading to enhanced TGFβ signaling [ 110 ].…”
Section: Features Of Ec Dysfunctionmentioning
confidence: 99%